2021
DOI: 10.1080/23311916.2021.1926406
|View full text |Cite
|
Sign up to set email alerts
|

Computational framework for the selection of energy solutions in indigenous communities in Colombia: Kanalitojo case study

Abstract: This study seeks to analyze different energy solutions for the Kanalitojo Indigenous Community that is located 25 kilometers from the municipal seat of the municipality of Puerto Carreño, in the State of Vichada, eastern Colombia. For the development of this study, a technical performance analysis has been applied to each proposed solution considering the amount of electricity generation and demand. The first solution refers to a hydrokinetic turbine connected to a distribution network. The second solution com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…They found that a 30 • inclination angle reduced the 𝐶 𝑃 from 0.45 to 0.35 and led to alternating stresses that increased fatigue strength. In tandem to optimization, several case studies have examined the applicability of hydrokinetic energy in different scenarios, including rivers, canals, coastal sea currents, irrigation systems, estuaries and outflows from pico and large hydropower plants [18][19][20][21][22][23][24][25][26][27]. Most of the works focused their analyses on Latin American countries (BR, Colombia, Ecuador and Mexico), with a lower contribution from Asia (Malaysia and India), Africa (South Africa), North America (California, Louisiana and Alaska) and Europe (Portugal and Austria).…”
Section: Introductionmentioning
confidence: 99%
“…They found that a 30 • inclination angle reduced the 𝐶 𝑃 from 0.45 to 0.35 and led to alternating stresses that increased fatigue strength. In tandem to optimization, several case studies have examined the applicability of hydrokinetic energy in different scenarios, including rivers, canals, coastal sea currents, irrigation systems, estuaries and outflows from pico and large hydropower plants [18][19][20][21][22][23][24][25][26][27]. Most of the works focused their analyses on Latin American countries (BR, Colombia, Ecuador and Mexico), with a lower contribution from Asia (Malaysia and India), Africa (South Africa), North America (California, Louisiana and Alaska) and Europe (Portugal and Austria).…”
Section: Introductionmentioning
confidence: 99%